2023
DOI: 10.3390/v15010249
|View full text |Cite
|
Sign up to set email alerts
|

HIV-HCV Incidence in Low-Wage Agricultural Migrant Workers Living in Ghettos in Apulia Region, Italy: A Multicenter Cross Sectional Study

Abstract: Migrant populations are more susceptible to viral hepatitis and HIV due to the epidemiology from their country of origin or their social vulnerability when they arrive in Europe. The aims of the study are to explore the incidence of HIV and HCV in low-wage agricultural migrant workers and their knowledge, attitude, and practice with regard to HIV and HCV, as well as their sexual behaviour and risk factors. As part of the mobile clinic services, we performed a screening campaign for HIV-HCV involving migrants l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In our study, which included 85 homeless people and 64 agricultural migrant workers living in Southern Italy, the cumulative prevalence of STI was high, and only half of the overall population returned to collect test results. Overall knowledge of STI modes of transmission was low and, in line with other studies [18,19], only 14% of the population reported consistent condom use.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, which included 85 homeless people and 64 agricultural migrant workers living in Southern Italy, the cumulative prevalence of STI was high, and only half of the overall population returned to collect test results. Overall knowledge of STI modes of transmission was low and, in line with other studies [18,19], only 14% of the population reported consistent condom use.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, Popping [ 6 ] stressed the role of knowing the transmission dynamics of HCV for targeted prevention strategies. Totaro and colleagues [ 7 ] underline how migrants in Italy have low HCV knowledge, confirming migrants as a population with a higher risk of infection. These studies can help to develop education programmes, integrated care, and screening among migrants, which could be an effective strategy.…”
mentioning
confidence: 99%